n → ∞ lim ln ⎣ ⎡ 2 n 1 k = 1 ∏ n ( 2 + n 2 k ) ⎦ ⎤ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
in this case, why we cannot directly put "n=infinity" after expanding ??
nice sandwich theorom problem
Problem Loading...
Note Loading...
Set Loading...
We have that: ln [ 2 n 1 k = 1 ∏ n ( 2 + n 2 k ) ] = k = 1 ∑ n ln ( 1 + 2 n 2 k )
and since x − 2 x 2 < ln ( 1 + x ) < x ∀ x > 0
then k = 1 ∑ n 2 n 2 k − 2 1 k = 1 ∑ n 4 n 4 k 2 < ln [ 2 n 1 k = 1 ∏ n ( 2 + n 2 k ) ] < k = 1 ∑ n 2 n 2 k .
But k = 1 ∑ n 2 n 2 k = 2 n 2 1 k = 1 ∑ n k = 4 n 2 n ( n + 1 ) ⟶ 4 1
and k = 1 ∑ n 4 n 4 k 2 = 4 n 4 1 k = 1 ∑ n k 2 = 2 4 n 4 n ( n + 1 ) ( 2 n + 1 ) ⟶ 0
So n → ∞ lim ln [ 2 n 1 k = 1 ∏ n ( 2 + n 2 k ) ] = 4 1 = 0 . 2 5